Marketing Transformation, Dynamic Capability, and Hospital Sustainability: Evidence from a Public Tertiary Referral Hospital in Indonesia - Gustantyo Wahyu Wibowo; Mahendro Prasetyo Kusumo (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Public hospitals in emerging countries face sustainability pressures due to high dependence on national health insurance reimbursement systems. Objective: This study examines how RSUP Dr. Kariadi Semarang, a public tertiary referral hospital in Indonesia, transformed hospital marketing into a strategic capability to support payer diversification and healthcare business sustainability. Methods: An embedded single-case study using descriptive quantitative indicators, this study analyzed secondary institutional data spanning 2024 to 2025, with comparative trend analysis focusing on the pre-transformation baseline (2024) and post-transformation period (2025), including strategic business plans, marketing performance reports, innovation documents, and financial indicators. Trend Growth Analytics was applied using growth rate, contribution ratio, payer diversification indicators, revenue composition analysis, and financial resilience indicators. Results: The findings show that non-JKN outpatient visits increased by 23%, non-JKN inpatient visits increased by 105%, and non-JKN revenue increased from IDR 110.35 billion in 2024 to IDR 233.18 billion in 2025. The contribution of non-JKN revenue to operational revenue increased from 8% to 16%, while EBITDA improved from negative IDR 10 billion to positive IDR 43 billion. These findings do not imply direct causality but indicate temporal associations and strategic contribution patterns between marketing transformation, payer diversification, and financial resilience. Conclusion: This study contributes to healthcare management literature by positioning hospital marketing transformation as a dynamic organizational capability supporting public hospital sustainability within emerging-country healthcare systems.